Electrochemical, Docking and Pharmacological Studies of Co(II), Ni(II), Cu(II) and Zn(II) Mixed Ligand Complexes - Leelavathy, Chellaian; Arulantony, Susaimanickam (Asian Journal of Chemistry, 2015)
Mixed ligand complexes of Co(II), Ni(II), Cu(II) and Zn(II) with Schiff base derived from the condensation of furfurylidene-4-aminoantipyrine and 2-aminobenzothiazole with 2-aminophenol have been synthesized and characterized by various analytical and spectral techniques. The in vitro antimicrobial screening of the ligand and its metal complexes were done. The interaction of the complexes with calf thymus DNA (CT DNA) has been investigated by UV absorption method. In addition, the DNA cleavage activity of the complexes was studied using agarose gel electrophoresis in the presence of H2O2 as oxidant. Super oxide dismutase activities of the mixed ligand complexes have also been measured. Cytotoxicity and in vitro anticancer studies of the complexes using MTT assay were also done. Molecular docking was used to determine the binding mode of the mixed ligand complexes to glucosamine-6-phosphate synthase.